2022
DOI: 10.1039/d2cp02448a
|View full text |Cite
|
Sign up to set email alerts
|

Iron L3-edge energy shifts for the full range of possible 3d occupations within the same oxidation state of iron halides

Abstract: Oxidation states are integer in number but dn configurations of transition metal centers vary continuously in polar bonds. We quantify the shifts of the iron L3 excitation energy, within the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
4
10
0
Order By: Relevance
“…13 From the median L 3 excitation energy of 642.6 ± 0.2 eV, also shown in Fig. 1(a) as a dashed black line, we can deduce the oxidation state 28 of the manganese center in [OMnO] + to be +5 in agreement with the earlier report, 13 cf . ESI,† Fig.…”
Section: Resultssupporting
confidence: 91%
“…13 From the median L 3 excitation energy of 642.6 ± 0.2 eV, also shown in Fig. 1(a) as a dashed black line, we can deduce the oxidation state 28 of the manganese center in [OMnO] + to be +5 in agreement with the earlier report, 13 cf . ESI,† Fig.…”
Section: Resultssupporting
confidence: 91%
“…The shift toward higher excitation energy could be induced by a reduced fractional 3d occupation in Mn II (acac) 2 still representing the same oxidation state of +2. 75 However, in both cases the X-ray absorption spectrum at the Mn L 2,3 edges could reasonably well be reproduced by CF simulations only and DFT calculations give the same Mulliken spin population 63 indicating the same or at least very similar 3d occupation in both cases. It previously has been shown that the excitation energy systematically decreases within one oxidation state when decreasing the average coordination of the metal center.…”
Section: Resultsmentioning
confidence: 80%
“…There is a striking difference in the L 3 excitation energy of 0.8 eV for oxidation state +2 when comparing neutral Mn II (acac) 2 and cationic Mn II (acac) 1 + . The shift toward higher excitation energy could be induced by a reduced fractional 3d occupation in Mn II (acac) 2 still representing the same oxidation state of +2 . However, in both cases the X-ray absorption spectrum at the Mn L 2,3 edges could reasonably well be reproduced by CF simulations only and DFT calculations give the same Mulliken spin population indicating the same or at least very similar 3d occupation in both cases.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the ruthenium M 3 excitation energy median of [RuO 4 H] + , included in Figure 3, is 466.7 � 0.3 eV, which matches the ruthenium M 3 edge median of [RuO 4 ] + of 466.3 � 0.3 eV within the error bars. Here, the 0.35 eV difference between [RuO 4 ] + and [RuO 4 H] + ruthenium M 3 edge median is considered to be in the range of chemical shifts observed at the L 3 edge median within a same oxidation state of iron with halogen ligands of different electronegativity, [50] as should also be the case for oxido and hydroxido ligands. [50] Hence, the ruthenium M 3 edge median of [RuO 4 H] + is consistent with the ruthenium center in the same oxidation state of + 8 as in [RuO 4 ] + , and, therefore, with the predicted structure of [Ru(O) 3 (OH)] + , since hydrogenation adds an electron to the oxygen-centered SOMO of [RuO 4 ] + , with only little metal character, but does not induce a chemical shift at the ruthenium M 3 edge.…”
Section: Quenching the Oxygen-centered Radical: Oxygen K Edge Spectra...mentioning
confidence: 99%